La inconstitucionalidad de la resolución del consejo nacional de la niñez y adolescencia con respecto a la tabla de fijación de pensiones - Maigualca Macato, Marlene del Rocío (2011)
The setting of maintenance has now become a topic of social relevance in which we as a society involving all. The present investigation aims to reveal the true situation in which parents are involved with regard to trials for the establishment of maintenance we believe it is very sharp and gives no option to the obligor to present exculpatory evidence in its favor to be imposed on him a pension based on their net income; resulting in a breach of the guarantee of the right to defend itself that is stipulated in the Constitución de la República del Ecuador that is why we have seen the need to seek the Unconstitutionality of the Resolution Of the National Counsel of the Childhood and Adolescence with relation to the table of alimony to be conspicuous disregard of the true economic reality, social and judiciary of the country and citizens. The scope of this research is to offer and contribute to society with a more feasible for the development of trials and especially in the implementation of maintenance without violating the rights of parents.